Sobre la naturaleza del delito de colusión del artículo 384 del Código Penal: Análisis del debate jurisprudencial - Chanjan Documet, Rafael; Espinoza Marmolejo, Omar; Avendaño Cotrina, María Luisa; Santa María Alcázar, Felipe; Choque Moya, Alonzo; Gutiérrez Hinojosa, Lucrecia Samantha; Vega Malpartida, Adler Donnovan (Pontificia Universidad Católica del Perú, 2022)
This article analyzes the nature of the crime of collusion regulated in article 384 of the Peruvian Penal Code, based on the recent jurisprudence of the Supreme Court of Justice. The relationship between the illicit of the first paragraph of the aforementioned article -called “simple collusion”- and the second paragraph -called “aggravated collusion”, its protected objects and its nature of crimes of injury or danger will be examined. On this point, a critical analysis of some jurisprudential pronouncements will be made and a position will be adopted on the autonomous nature of both crimes in order to solve practical problems such as the moment of consummation of the crime, the attempt and criminal participation.

El presente artículo analiza la naturaleza del delito de colusión regulado en el artículo 384 del Código Penal peruano, a la luz de la reciente jurisprudencia de la Corte Suprema de Justicia. Se examinará la relación existente entre el ilícito del primer párrafo del referido artículo -denominado “colusión simple”- y el segundo párrafo -denominado “colusión agravada”-, sus bienes jurídicos protegidos y su naturaleza de delitos de lesión o de peligro. Sobre este punto, se efectuará un análisis crítico de algunos pronunciamientos jurisprudenciales y se adoptará una postura sobre la naturaleza autónoma de ambos ilícitos a fin de solucionar problemáticas prácticas como el momento de consumación del delito, la tentativa y la participación delictiva.
About the nature of the crime of collusion of article 384 of the Criminal Code: Analysis of the jurisprudential debate
Keywords: Colusión; Colusión agravada; Delitos de lesión; Delitos de peligro naturaleza autónoma; Consumación; Tentativa; Participación delictiva; Collusion; Aggravated collusion; Crimes of injury; Crimes of danger; Autonomous nature; Consummation; Attempt; Criminal participation; https://purl.org/pe-repo/ocde/ford#5.05.00